Ideologías lingüísticas en el campo de la traducción - Achaya Ormeño, Maria Fernanda (2022)
This article aims to explore the role and consequences of language ideologies in Translation. To do so, I focus on three levels: translation theory, the Translator, and the institutional and social sphere. In addition, the article is based on the studies done by Lee (2013), Andrade et al. (2017) and Angermeyer (2015). The conclusions suggest that, in the first place, the relation between Translation theory and language ideologies relies on the influence of cultural identity and power relationships within society. Regarding the Translators’ role, they can transfer their language ideologies through the way they translate. These ideologies can also be found in social and institutional spheres, and many of them weaken concrete actions in favor of specific citizens.